2012
DOI: 10.1111/j.1365-2753.2012.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Information‐searching behaviors of main and allied health professionals: a nationwide survey in Taiwan

Abstract: This national survey depicts the information-searching pattern of various health professionals. There were significant differences between and within main and allied health professionals in their information searching. The data provide clinical implications for strategies to promote the accessing of evidence-based information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Searches made in Google, or similar search engines, are mentioned in eight of the nine studies, (Baro & Ebhomeya, ; Chiu et al., ; Kumaran & Chipanshi, ; Miller, Graves, Jones, & Sievert, ; Muallem, ; Ross, ; Wahoush & Banfield, ; Weng et al., ) representing a total of 6572 respondents. The studies conclude that the majority of the nurses use Google to search for information, including evidence based and health information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Searches made in Google, or similar search engines, are mentioned in eight of the nine studies, (Baro & Ebhomeya, ; Chiu et al., ; Kumaran & Chipanshi, ; Miller, Graves, Jones, & Sievert, ; Muallem, ; Ross, ; Wahoush & Banfield, ; Weng et al., ) representing a total of 6572 respondents. The studies conclude that the majority of the nurses use Google to search for information, including evidence based and health information.…”
Section: Resultsmentioning
confidence: 99%
“…Among the bibliographic databases, PubMed or MEDLINE is the most frequently used and included in seven of the nine studies (Chiu et al., ; Hunt, Cimino, & Koziol, ; Miller et al., ; Muallem, ; Ross, ; Wahoush & Banfield, ; Weng et al., ) representing 6429 respondents. Three of the studies reported percentages on the use of PubMed or MEDLINE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our study demonstrated that the increased usage of online database was proportional to that of Web portals. We found the majority of physicians and nurses used the online database for self-learning or clinical practice [28,29]. However, we did not know why they accessed the Web portals.…”
Section: Discussionmentioning
confidence: 99%